(untitled) (Forum Theologicum Sardicense, 2025)
Nevjana Rizova, To the Problem of the Interpretative Method in “Gospel of Christian Glory in the Apocalypse” by N. N. Glubokovsky The author provides a brief overview of Glubokovsky’s work Gospel of Christian Glory in the Apocalypse, focusing specifically on Glubokovsky’s exegetical approach to interpreting the Revelation of St. John.